PENGARUH FINANCIAL PRESSURE, STABILITY DAN TARGET TERHADAP FINANCIAL STATEMENT FRAUD - Indra Lukmana Putra (RISTANSI: Riset Akuntansi, 2022)
The purpose of this study was to investigate the effect Financial Pressure, Stability dan Target on financial statement fraud. The study population consisted of Infrastructure, Utilities and Transportation companies on the Indonesia Stock Exchange (IDX) from 2018-2020.The sampling technique used was purposive sampling.The method used in this research is quantitative research methods. The data source consists of secondary data obtained from the Indonesia Stock Exchange (IDX). The result showed that financial stability had a significant effect on financial statement fraud, indicating that companies that have pressure can enhance fraud behavior.